2016
DOI: 10.1152/ajpgi.00305.2015
|View full text |Cite
|
Sign up to set email alerts
|

The human milk oligosaccharide 2′-fucosyllactose augments the adaptive response to extensive intestinal

Abstract: Intestinal resection resulting in short bowel syndrome (SBS) carries a heavy burden of long-term morbidity, mortality, and cost of care, which can be attenuated with strategies that improve intestinal adaptation. SBS infants fed human milk, compared with formula, have more rapid intestinal adaptation. We tested the hypothesis that the major noncaloric human milk oligosaccharide 2'-fucosyllactose (2'-FL) contributes to the adaptive response after intestinal resection. Using a previously described murine model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 65 publications
0
20
0
1
Order By: Relevance
“…This species has previously been shown to have anti-obesogenic effects by enhancing gut integrity, ameliorating intestinal and systemic inflammation and improving lipid metabolism via increased adipose tissue thermogenesis [46]. Ethan et al also reported a four-fold increase in the abundance of genus Parabacteroides in mice supplemented with 2 -FL after ileocecal resection [54].…”
Section: Discussionmentioning
confidence: 98%
“…This species has previously been shown to have anti-obesogenic effects by enhancing gut integrity, ameliorating intestinal and systemic inflammation and improving lipid metabolism via increased adipose tissue thermogenesis [46]. Ethan et al also reported a four-fold increase in the abundance of genus Parabacteroides in mice supplemented with 2 -FL after ileocecal resection [54].…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, GOS/FOS, but not 2′-FL intervention, promoted body weight gain at the end of the study regardless of the infective process. There is not a clear conclusion about the effects of the products on animal growth, as some studies find differences (Mezoff et al, 2016 ; Charbonneau et al, 2017 ) and some others not (Lima et al, 2017 ; Rasmussen et al, 2017 ; Rigo-Adrover et al, 2017b ). Moreover, 2′-FL did promote the growth of the small intestine, which had a bigger percentage of the total body weight after 7 days of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating of gut microbiota following intestinal resection improved the outcome of short bowel syndrome in an experimental setting. Supplementation with 2′-FL increased weight gain following ileo-cecal resection and promoted histological changes in gut mucosa suitable for adaptation [ 71 ].…”
Section: Preclinical and Observational Studiesmentioning
confidence: 99%